Cadmium Level, Glycemic Control, and Indices of Renal Function in Treated Type II Diabetics: Implications for Polluted Environments - Anetor, John I.; Uche, Chukwuemelie Z.; Ayita, Emmanuel B.; Adedapo, Solomon K.; Adeleye, Jokotade O.; Anetor, Gloria O.; Akinlade, Sola K. (Frontiers in Public Health, 2016)
ABSTRACT: Cadmium (Cd) has recently emerged as a major concern not only in environmental toxicology but also in metabolic diseases such as diabetes mellitus (DM) and its complications. Conflicting data aside, these studies have not been examined in a clinical population undergoing management as well as possible modulation by the prominent metabolic antagonist of Cd such as zinc (Zn). This study examined the relationship between cadmium levels, glycemic control and renal pathology in established type II diabetic patients with focus on populations exposed to modern environmental health hazards (MEHHs). Sixty-five participants, consisting of 45 type-2 diabetics and 20 non-diabetics were enrolled for the study, mean age 61.51 ± 5.27 years. Glycated haemoglobin (HbA1C) was used to classify them into three sub-groups; (A) good glycemic control (44.4%), (B) fair glycemic control (24.4%) and (C) poor glycemic control (31.1%). Plasma levels of glucose, Cd, Zn, HbA1C, creatinine, urinary creatinine, microalbuminuria and estimated glomerular filtration rate (e-GFR) were determined in all participants using standard methods. Fasting plasma glucose (FPG), was higher in diabetics than in non-diabetics (p= 0.000) as well as Zn level, though not significantly. Interestingly, Cd Level, Cd/Zn ratio and Urinary creatinine were significantly lower in diabetics than in non-diabetics. The group with poor glycemic control (C) had significantly higher Cd level compared to the one with good glycemic control (group A). The renal function revealed that microalbuminuria and Urinary albumin/creatinine ratio (UACR) was significantly higher in diabetics than in non-diabetics while e-GFR was found to be similar in both diabetics and non-diabetics. UACR inversely correlated with Cd level, while Plasma creatinine level positively correlated to Cd but not significantly. Correlation between Cd and HbA1C revealed non-significant inverse correlation (r = -0.007; p> 0.05), while Zn showed a significant inverse correlation with Cd (r= - 0.317; p<0.014). The lower Cd level in diabetics compared to non-diabetics probably reflects the modulating effect of Zn in treated diabetics given nutritional education in addition to their regular regime including good sources of Zn. The renal insufficiency with increasing Cd level may suggest that the progression of renal impairment may not be responsive to the